Bibliometric and bibliographical study on optimizations in natural gas liquid (NGL) recovery processes (Research, Society and Development, 2019)
The growing worldwide need for energy coupled with the demand for natural gas that has economic and environmental advantages over other fossil fuels is a stimulus to apply energy efficiency in processing. This work investigated the scientific production related to the optimization of the Natural gas liquids (NGL) recovery process using software Hysys simulator. Several authors have focused not only on energy, exergy, sensitivity, economic and environmental analysis, but also on configuration and integration strategies to reduce energy consumption and maximize profitability. It is noticed that the absolute majority of the selected works came from countries of the Middle East, which means an opportunity for Brazilians to advance studies that contemplate the reality of the national plants.